Immune responses elicited by the GEN-003 candidate HSV-2 therapeutic vaccine in a randomized controlled dose-ranging phase 1/2a trial. Issue 44 (17th October 2016) - Flechtner, Jessica Baker; Long, Deborah; Larson, Shane; Clemens, Veronica; Baccari, Amy; Kien, Lena; Chan, Jason; Skoberne, Mojca; Brudner, Matthew; Hetherington, Seth
Highlights: Cellular and humoral responses were boosted in GEN-003 vaccinated HSV-2 seropositive subjects. Matrix-M2 adjuvant potentiated the immune responses to ICP4 and gD2 antigens contained in GEN-003. No immune correlates of anti-viral activity have yet been identified. Abstract: Purpose: GEN-003 is a candidate therapeutic HSV-2 vaccine containing a fragment of infected cell protein 4 (ICP4.2), a deletion mutant of glycoprotein D2 (gD2ΔTMR), and Matrix-M2 adjuvant. In a dose-ranging phase 1/2a clinical trial, immunization with GEN-003 reduced viral shedding and the percentage of reported herpetic lesion days. Here we examine the immune responses in the same trial, to characterize vaccine-related changes in antibody and cell-mediated immunity. Methods: Participants with genital HSV-2 infection were randomized to 1 of 3 doses of GEN-003, antigens without adjuvant, or placebo. Subjects received 3 intramuscular doses, three weeks apart, and were monitored for viral shedding, lesions and immunogenicity. Antibody titers were measured by ELISA and neutralization assay in serum samples collected at baseline and 3 weeks post each dose. T cell responses were assessed pre-immunization and 1 week post each dose by IFN-γ ELISpot and intracellular cytokine staining. Blood was also collected at 6 and 12 months to monitor durability of immune responses. Results: Antibody and T cell responses increased with vaccination and were potentiated by adjuvant. Among the doses tested, the rank order of reduction in viral shedding follows the ranking of fold change from baseline in T cell responses. Some immune responses persisted up to 12 months. Conclusion: All measures of immunity are increased by vaccination with GEN-003; however, a correlate of protection is yet to be defined.